The effect of altitude and season on dielectrical relaxation mechanism of ionospheric plasma - Yesil, A.; Unal, I. (Soc Italiana Fisica, 2009)
In this paper, the effect of altitude and season on dielectrical relaxation mechanism of ionospheric plasma has been investigated. The real and imaginary parts of the dielectric constant with respect to altitude were seasonally calculated. The real and imaginary parts of the dielectric constant change with altitude and season, so the plasma frequency does. The imaginary part of the dielectric constant shows a relaxation peak and peak position shifts to lower altitudes. In the F region, the real part of the dielectric constant is very lower due to the excessive electron exchanges. This suggests that the determination of the dielectrical properties of the F-region is very important to explain the propagation of electromagnetic waves in the F region, because the propagation of electromagnetic waves in the F region is affected by the dielectrical properties of the ionosphere.